Self-regulated learning and personality in university students - Cepeda, Danna; Mahecha, Jenny (Revista Innova Educación, 2022)
The present investigation analyzes the relationship between the self-regulation of learning and the personality characteristics of university students belonging to the Minuto de Dios University Corporation - UNIMINUTO of Bogotá - Colombia the sample consisted of 75 men and women between 18 and 45 years of age. From the application of the instruments: Gordon's personality profile and inventory (ancestry, responsibility, emotional stability, sociability, caution, originality, commitment, vitality, and self-esteem) and the self-report questionnaire - self-regulation of learning, the correlational analysis was carried out. Using Spearman's Rho (significance level p
Keywords: learning; self-regulation; personality